PERAN KOMUNIKASI ORANG TUA DAN ANAK MENCIPTAKAN KELUARGA SAKINAH DAN BERAKHLAK - Budi Mulia (PIKTORIAL : Journal of Humanities, 2019)
ABSTRACT The development of technology and information offers a variety of creative and exciting opinions that are packaged very interesting, especially for the consumption of elementary school children. Today children are smarter looking for information via the internet through an internet rental, they want to access information without supervision from parents. The pattern of guidance and family attention that is lacking can affect the physical and mental aspects of the child. The school becomes the center of character and skill development, the effort to aim at education has such a way through additional curriculum as a characteristic of each school. Communication through the family becomes effective when parents are able to position themselves before their children. An effective effort and good and ongoing communication between parents and children is an important factor in knowing the difficulties or problems faced by his age. It has become important and how to form warm relationships with children. This research becomes important so that parents can make the sakinah family a means to discuss so that unwanted events do not happen to their children. Morals are the target of communication activities between parents and children in creating a happy family. Keywords: Parenting, communications, family, moral qur’anic